Participation of Potential Transient Receptors in the Antinociceptive Effect of Pharmacopuncture - Isabella de Paula Ribeiro Argôlo; Julia Risso Parisi; Josie Resende Torres da Silva; Marcelo Lourenço da Silva (Medical Association of Pharmacopuncture Institute, 2022)
Background : Despite the widespread clinical use of acupuncture in painful situations, the use of this treatment should be further clarified. Nociception is mediated by the activation of nociceptors, such as transient receptor potentials (TRPs). The family of TRPs includes TRPV1, TRPM8, and TRPA1, which can be stimulated by substances such as capsaicin, menthol, and methyl salicylate, respectively. Objectives: This study aimed to investigate the role of TRPs in antinociception via the administration of agonists of these receptors in the Zusanli acupoint (ST36) in models of inflammatory, acute, and neuropathic pain. Methods : Male Wistar rats were used for this experiment. All rats received a subcutaneous injection of TRP agonists (capsaicin, menthol, or methyl salicylate) in ST36; saline was injected as control. Nociception was evaluated using the electronic mechanical threshold test and tail-flick test before the administration of complete Freund's adjunct or chronic constriction injury of the sciatic nerve and after the administration of TRP agonists. Results : Nociception was found to be attenuated after treatment with TRP agonists. The administration of different doses (0.03, 0.3, and 3.0 μg/20 μL) of capsaicin, menthol, and methyl salicylate in the different pain models (neuropathic, inflammatory, and nociceptive) induced antinociception in most of the evaluated time points. Conclusion : Based on the findings, we suggest that the activation of TRPV1, TRPM8, and TRPA1 receptors results in the antinociceptive effect of the stimulation of the ST36 acupoint. Thus, TRP receptors may present a new therapeutic opportunity for the control of inflammatory and neuropathic pain.